Epilithic diatom community structure and physical-chemical interactions in Bolukcali stream (Elazig/Turkey) - Sonmez, Feray; Caglar, Metin (My University, 2011)
Epilithic diatoms of Bolukcali stream were studied from February-December 2009 using samples collected from two stations. Sampling was performed monthly. Temperature, pH, dissolved oxygen, nitrate, orthophosphate and silica values were measured over the entire study period. Epilithic diatoms of Bolukcali stream consisted most commonly of Cyclotella, Cymbella, Navicula and Surirella genera while other genera identified included Epithemia, Nitzschia, Rhoicosphenia, Gomponema and Cocconeis. The physical and chemical parameters of these diatom communities were studied along with their variations by stations and seasons. © Medwell Journals, 2011.
Keywords: Bolukcali stream; Dissolved oxygen; Elazig; Epilithic diatom; Parameter; Seasonal variation